Enhancement of plasticity for FeCoBSiNb bulk metallic glass with superhigh strength through cryogenic thermal cycling. (October 2020) - Di, Siyi; Wang, Qianqian; Zhou, Jing; Shen, Yiyang; Li, Jiaqi; Zhu, Mingyun; Yin, Kuibo; Zeng, Qiaoshi; Sun, Litao; Shen, Baolong
Abstract: The mechanical properties and atomic-scale structure of the [(Fe0.5 Co0.5 )0.75 B0.2 Si0.05 ]96 Nb4 bulk metallic glass (BMG) treated with cryogenic thermal cycling were studied. The obtained Fe-based BMG shows an improvement of plastic strain from 1.4 to 6.1% and maintains a high yield strength over 4000 MPa. The high structural disorder degree caused by rejuvenation, as well as the fine-tuned crystal-like ordering structures induced by internal stress, contribute to the formation of multiple shear bands, and thus results in the enhancement of plasticity. This work provides a new insight to develop plastic Fe-based BMGs through modulating atomic-scale structure. Graphical abstract: Image, graphical abstract